USING THINK-PAIR-SHARE TECHNIQUE TO IMPROVE STUDENTS’ PARTICIPATION IN WRITING DESCRIPTIVE TEXT - R, Hanifah A; Sofian, Sofian; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to improve students’ participation in writing descriptive text by using Think-Pair-Share technique to class VII of Madrasah Tsanawiyah Raudhatul Ulum 1 Meranti. The research method used was a classroom action research which consisted of two cycles. Each cycle consisted of planning, acting, observing and reflecting. The subject of this research was the seventh grade students of Madrasah Tsanawiyah Raudhatul Ulum 1 Meranti which consisted of 30 students. In collecting the data, the researcher used observation checklist and field note. The result of the research showed that most of the students could reach the standard criteria of students’ participation in writing skill which the mean score was 79%. It was qualified as good to excellent. Based on the result, it can be concluded that using Think-Pair-Share technique improves students’ participation in writing descriptive text. Keywords: Think-Pair-Share, students’ participation, descriptive text